Recent trends and developments in social software International Conferences on Social Software, BlogTalk 2008, Cork, Ireland, March 3-4, 2008, and BlogTalk 2009, Jeju Island, South Korea, September 15-16, 2009 : revised selected papers - International Conference on Social Software (2008 Cork, Ireland); Breslin, John G. (John Gerard).; SpringerLink (Online service). (Berlin Springer, 2010)
BlogTalk, the International Conference on Social Software, brings together different groups of people using and advancing the Internet and its usage: technical and conceptual developers, researchers with interdisciplinary backgrounds, and practitioners alike. The focus is on social software as an expression of a culture that is based on the exchange of information, ideas and knowledge. The present volume includes 6 papers from BlogTalk 2008 as well as 11 papers from BlogTalk 2009. The areas discussed include: forms and consequences of emerging social software practices; social software in enterprise and educational environments; the political impact of social software; applications, prototypes, concepts and standards.
Electronic reproduction.
Keywords: Social media -- Congresses; Computer network resources -- Congresses; Blogs -- Social aspects -- Congresses; Electronic books